Shiny application for consulting data online - Montes, Carlo; Gómez, Francisco (International Maize and Wheat Improvement Center, 2023)
Shiny application uses the API of Worlclim data set (https://www.worldclim.org/data/index.html) for getting climate data with coordinates taken by clicking on an interactive map or by typing on a text box. The applications uses WorldClim version 2.1, which contains monthly averages data calculated with climate data from 1970 to 2000, the resolution of data is available for three resolution size: 4.6km (2.5 minutes), 9.2 km (5 minutes) and 18.5 km (10 minutes). monthly averages. Each data represents a square surface (called pixel), which length per side is the resolution mentioned above. The climate variables available for downloading are: Maximum temperature, Minimum temperature, Mean temperature and Rainfall. Elevation data is also available, derived from SRTM elevation data, for the same resolution mentioned above.